PENGEMBANGAN PROBLEM SOLVING DAN SIKAP ILMIAH SISWA DENGAN BAHAN AJAR IPA BERPENDEKATAN AUTHENTIC INQUIRY LEARNING - Widowati, Asri; Nurohman, Sabar; Anjarsari, Putri (Universitas Negeri Yogyakarta, 2017)
The aims of this activity are: (1) to disseminate the results of research from a team of stewards on the development of learning materials authentic inquiry based learning to develop problem solving and scientific attitude; (2) to develop the skills of teachers in guiding students for doing investigation or inquiry; (3) to develop the skills of teachers in developing learning material with authentic inquiry approach; (4) to develop the skill of teachers in teaching with implementation of authentic inquiry leaning approach. The target participant of this activity is 26 teacher members of MGMP IPA SMP Magelang regency. This activity is done in three stages, including the stage of theoretical training, practical training phase and the evaluation phase. The methods used are: lecture, modeling, discussion, and workshop. The results showed that the overall activity of PPM activity has been successful in reaching the target activity. Most of the participants are already skilled in guiding student for doing inquiry. Most participants also been able to develop student worksheet based on authentic inquiry learning approach and half of student worksheets have contain of problem solving and scientific attitude development. Most of the group of participant can teaching science through the authentic inquiry approach very Good because most of the steps of authentic inquiry learning approach has be done by all group